2009
DOI: 10.1590/s0100-40422009000700016
|View full text |Cite
|
Sign up to set email alerts
|

Flow-injection spectrophotometric determination of tetracycline and doxycycline in pharmaceutical formulations using chloramine-T as oxidizing agent

Abstract: for TC and DXC, respectively. The analytical frequency was 50 h −1 and 45 h -1 for TC and DXC, respectively. The results obtained by the proposed method were in good agreement with those obtained by the official method at 95% confidence level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Tetra-cyclines are active against a wide range of gram-negative and gram-positive organisms [1]. Several analytical methods have been reported for the determination of TCH in raw material and dosage forms include spectrophotometry [2,3], flow injection [4], voltametry [5], and HPLC methods [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tetra-cyclines are active against a wide range of gram-negative and gram-positive organisms [1]. Several analytical methods have been reported for the determination of TCH in raw material and dosage forms include spectrophotometry [2,3], flow injection [4], voltametry [5], and HPLC methods [6].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of OTC in pharmaceuticals by FIA coupled with spectrophotometry detection is also reported in the literature (Rufino et al, 2009;Al-Momani and Kanan, 2008;Medina et al, 2000;Karl ı cek and Solich, 1994;Alwarthan et al, 1991). A recent methodology for direct quantification of OTC in veterinary pharmaceuticals using continuous FIA with spectrophotometric detection was developed by Rodr ıguez and colleagues (2016).…”
Section: Flow Injection Analysismentioning
confidence: 94%
“…The analytical procedures based on spectrophotometry [19][20][21] are still being frequently published in the literature. Literature survey revealed that few spectrophotometric methods have been used to determine haloperidol in pharmaceutical preparations.…”
Section: Introductionmentioning
confidence: 99%